Crash Beam - Barrett, John; Vestal, Herman B., 1916-2007 (Salt Lake City, UT : Project Gutenberg, 2021)
"Crash Beam" by John Barrett is a science fiction novel written in the late 1940s. The story centers around a perilous incident involving landing rockets on a futuristic Earth-Venus space route, where a sudden catastrophe threatens the lives of pilots and passengers alike. The narrative explores themes of technology, sabotage, and the desperate struggle to avert disaster in a high-stakes environment. The plot unfolds as Dan Kearns, an electronics engineer, faces the aftermath of a disastrous landing mishap that results in the death of two pilots. As he grapples with the implications of control failures, Kearns uncovers evidence suggesting that the incidents are not the result of mere technical issues but possibly the work of sabotage involving dangerous light wavelengths. As the clock ticks down to the arrival of another passenger rocket, Kearns must act fast, ultimately taking control of the situation by reflecting the harmful beam back at its source, exposing the treachery that threatened their mission. The story combines tension-filled moments with a clever twist on the intersection of human ingenuity and technological hazard. (This is an automatically generated summary.)
Release date is 2021-01-11
Greg Weeks, Mary Meehan and the Online Distributed Proofreading Team at http://www.pgdp.net
Keywords: Science fiction; Short stories; Space flight -- Fiction; Engineers -- Fiction; Sabotage -- Fiction